Gross precipitation and throughfall chemistry in legume species planted in Northeastern México - Návar, José; Méndez González, Jorge; Gonzalez, Humberto (Springer Nature, 2009)
Plant cover modifies throughfall chemistry, and the solute concentration is dependent on the plant species at any given site. The chemistry of gross rainfall and throughfall of four endemic species planted in northeastern Mexico was evaluated from March 1996 to March 1997. Chemical solutes measured included Ca, K, Mg, Na, Fe, Mn, Cu, and Zn. Dry deposition and canopy leaching fluxes were estimated following the canopy budget model. Variance analyses tested the statistical dependence of the total and net fluxes on the species and seasons. Regression analysis tested the dependence of chemical concentrations on rainfall depth and lag time between rains. A total of 52 rainfall events were recorded during the study period summing 523 mm. Significant differences were noted on the total and net fluxes between the plant species. For total flux, average throughfall (37.8 kg ha−1 year−1 ) almost doubled the flux of solutes compared to rainfall (24.1 kg ha−1 year−1). Pithecellobium ebano (Berland.) C.H. Mull. (43.3 kg ha−1 year−1), Acacia berlandieri Benth. (38.7 kg ha−1 year−1), and Pithecellobium pallens (Bent.) Standl. (38.4 kg ha−1 year−1 ) recorded the highest total flux of solutes, and Acacia rigidula Benth. (30.9 kg ha−1 year−1) the smallest. Chemical solutes showed significant differences for total and net fluxes. Ca was the dominant cation with 48% and 52% of the total constituent flux for rainfall and throughfall, respectively. However, K, Mg and Cu approximately doubled in throughfall in contrast to gross rainfall. Species with the largest aboveground biomass had lower throughfall volumes (i.e., higher interception rates) but higher chemical solute inputs to the forest floor. Rainfall depth and lag time between rains explained part of the variation for most species, stressing the partial dependence of the washing effect and the amount of dry deposition on canopies. This research discusses the importance and the sources of incoming solutes on the studied plant species.